Morpho-Physiological Characters and Soybean Productivity on Alfisol and Vertisol under Intercropping with Kayu Putih (Melaleuca cajuputi) - Suryanto, Priyono; Putra, Eka Tarwaca Susila; Suwignyo, Bambang; Prianto, Sukirno Dwiasmoro; Alam, Taufan (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
Intercropping kayu putih (Melaleuca cajuputi) has more advantage than other tree crops, such as teak, pine or acacia due to the beneficial intercropping season length.Â Soybean was intercropped with kayu putih because soybean has higher commercial value than other field crops. The survey-based research was conducted during March until May, 2014 in Menggoran Forest Resort, Playen Forest Section, Yogyakarta Forest Management District. Stratified random sampling method was used during the research by stratifying the types of soil stratification (alfisol and vertisol), rainfall and declivity then was made into 7 land mapping unit (LMU) with map overlay technique. Agronomic characters of soybean were observed on 12 weeks after planting (wap) and the physiological data were observed during the maximum vegetative phase (8 wap). Agronomic and physiological characters of soybean in each LMU were grouped and statistically tested with analysis of variance (ANOVA) then continued with orthogonal contrasts (alpha 5%). The results showed that some characters of soybean planted in alfisol had higher value than in vertisol, especially on leaf area, photosynthetic rate, root and canopy weight, 100 grain weight and grain weight per plant. The agronomic and physiological characters of soybean which had significant effects on yield in the intercropping with kayu putih system were stomatal density, stomatal conductivity, photosynthetic rate, and leaf area. Soybean intercropped with kayu putih produced 1.007 tons/ha in alfisol and 0.996 tons/ha in vertisol. Soybean development in intercropping system of kayu putih can be conducted by using soybean varieties superior effort.